Social history of Capoeira through images. The Raul Pederneiras’ "silhouettes" (Revista de Artes Marciales Asiáticas, 2017)
The study of Capoeira through the interpretation of images is characterized by being practically non-existent, and contains superficial and scarcely informed interpretations of its presence in Brazil. This study is based on the historical method and also is supported by the principles of the Historical Archaeology (Orser Jr., 1992) and those developed by Panofsky (1986) on the interpretation of images. For this study, we selected an iconography- "Silhouette" - by Pederneiras (1926). From this artist’s work and the accompanying text it is highlighted the apology of Brazilian's fight and its supremacy over other self-defense expressions known at the time in Brazil, the recognition of the potential of Capoeira as a physical exercise, and Pederneira’s comments on some contextual facts, highlighting the interference of its practitioners in Brazilian politics and their role as bodyguards recruited by politicians. He also referred its most famous practitioners, the gangs of Capoeira and their typical language and costumes in the Carioca society of the late 19th and early 20th century. This information, and specially the strokes depicted in the image, allows us to reconstruct the history of Capoeira movements, given the scarcity of historical sources in this field. Through this silhouette, Pederneiras sought to raise awareness among government authorities to adopt the Brazilian fight as a national identity element and recognize it as the National Gymnastics.